The Frontier Crimes Regulation in Colonial India: Local Critiques and Persistent Effects. Issue 4 (2nd October 2018) - Pant, Saurabh
Abstract: In their pursuit of self-serving goals, sometimes governments create and use various instruments as the means to relatively short-term ends. Such instruments, however, can be tenacious, and have perverse, long-lasting impacts. This paper focuses on one such instrument created during the British Raj: the Frontier Crimes Regulation. Often, the literature on the Regulation focuses on the rationale for its creation from the perspective of the colonisers and refers to the long-term consequences in hindsight, thereby ignoring local voices. However, I show that in 1901, at the time of the drafting of the Regulation, the local colonised population foresaw the potentially lasting pernicious effects stemming from it and voiced their concerns. I demonstrate that these local voices can help us understand the roots of the problems in the Federally Administered Tribal Areas (FATA) of Pakistan today.